2012
DOI: 10.1007/s00442-012-2483-9
|View full text |Cite
|
Sign up to set email alerts
|

Tissue turnover and stable isotope clocks to quantify resource shifts in anadromous rainbow trout

Abstract: Stable isotopes can illuminate resource usage by organisms, but effective interpretation is predicated on laboratory validation. Here we develop stable isotope clocks to track resource shifts in anadromous rainbow trout (Oncorhynchus mykiss). We used a diet-switch experiment and model fitting to quantify N stable isotope (δ(15)N) turnover rates and discrimination factors for seven tissues: plasma, liver, fin, mucus, red blood cells, muscle, and scales. Among tissues, diet-tissue δ(15)N discrimination factors r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
149
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 132 publications
(162 citation statements)
references
References 37 publications
13
149
0
Order By: Relevance
“…This strong influence of growth on isotopic turnover has also been reported for ectothermic animals more generally (e.g. MacAvoy et al, 2001;Perga & Gerdeaux, 2005;Heady & Moore, 2013) and is attributed to them having lower metabolic activities than endotherms (Bosley et al, 2002;Tominaga et al, 2003). Indeed, Perga and Gerdeaux (2005) suggested that as fish, and other ectotherms, have a discontinuous pattern of growth over the year, the stable isotope values of their muscle might only reflect their food consumed during periods of growth.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…This strong influence of growth on isotopic turnover has also been reported for ectothermic animals more generally (e.g. MacAvoy et al, 2001;Perga & Gerdeaux, 2005;Heady & Moore, 2013) and is attributed to them having lower metabolic activities than endotherms (Bosley et al, 2002;Tominaga et al, 2003). Indeed, Perga and Gerdeaux (2005) suggested that as fish, and other ectotherms, have a discontinuous pattern of growth over the year, the stable isotope values of their muscle might only reflect their food consumed during periods of growth.…”
Section: Discussionmentioning
confidence: 55%
“…Where experimental studies have been completed on larger or older fishes, and those with lower specific growth rates, the results suggest that metabolic replacement contributes a major proportion of total turnover, in some cases accounting for 80% of isotopic change in dorsal muscle (Suzuki et al, 2005;Logan et al, 2006;Tarboush et al, 2006). Heady and Moore (2013) revealed that catabolism contributed more to 15 N turnover in tissues with faster turnover rates, contributing 68% for fin compared to 0.7% for scales. Experimental design, especially the temperature used, can also significantly impact turnover rates, with higher water temperatures reducing the half-lives of the carbon stable isotope of muscle in similar sized fish (Bosley et al, 2002;Witting et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations